Protecting Adolescents in Indonesia from the Dangers of Smoking and Tobacco Products: A Narrative Review and Policy Implementation Perspectives - Fenny Etrawati; Rita Damayanti (The Indonesian Institute of Science and Technology Research, 2026)
The World Health Organization states that the prevalence of tobacco product use among young people aged 15-24 is 13.3%, while in Indonesia reached 47.1%. Smoking has an impact on morbidity and mortality due to degenerative and infectious diseases, lost work productivity due to illness, and health care financing. It is necessary to understand what policy strategies are in place to protect adolescents from the dangers of smoking and tobacco products. This study uses a narrative review approach with a broad focus on identifying the problem of adolescent smoking in Indonesia, policy responses, gaps in the literature, and strategies for improving policy implementation. The increasing trend of cigarette and tobacco product use among Indonesian adolescents indicates the need for effective strategies to accelerate the implementation of global commitments to reduce it. In line with the mandate of the Framework Convention on Tobacco Control (FCTC), six (6) MPOWER messages can be implemented, namely: monitoring tobacco use and prevention policies; protecting the community against cigarette smoke; offering support to quit smoking; warning of the consequences of smoking; enforcing bans on cigarette advertising, promotion, and sponsorship; and raising tobacco taxes. In addition, cross-programme and cross-sectoral cooperation is needed to implement existing policies more effectively and efficiently. These are expected to reduce smoking prevalence as well as improve healthcare efficiency.